2023
DOI: 10.1136/bmjopen-2022-069529
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling the predictors of late cancer presentation and diagnosis in Jordan: a cross-sectional study of patients with lung and colorectal cancers

Abstract: ObjectivesLate presentation or diagnosis of cancer results in a poor clinical prognosis, negatively affects treatment and subsequently lowers one’s chances of survival. This study aimed to identify the factors associated with late lung and colorectal cancer presentation and diagnosis in Jordan.DesignThis correlational cross-sectional study was based on face-to-face interviews and medical chart reviews from a cancer registry database. A structured questionnaire based on a review of the literature was used.Setti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 45 publications
0
1
0
Order By: Relevance
“…The incidence of timely diagnosis of lung cancer was 69%. This is lower than the study reported in Jordan [53]. This could be due to the difference in cut-off point used to…”
Section: Discussioncontrasting
confidence: 65%
“…The incidence of timely diagnosis of lung cancer was 69%. This is lower than the study reported in Jordan [53]. This could be due to the difference in cut-off point used to…”
Section: Discussioncontrasting
confidence: 65%
“…There is coverage through the Health Insurance Fund, the Military Health Insurance Fund, and private medical insurance. Studies that explored the impact of health insurance status on cancer outcomes in Jordan revealed that uninsured cancer patients faced greater financial burdens, leading to delays in appropriate cancer screening or seeking treatment compared to insured patients [ 56 , 57 ]. Lack of health insurance coverage is associated with higher rates of advanced-stage cancer at diagnosis and increased mortality rates among cancer patients [ 39 ].…”
Section: Resultsmentioning
confidence: 99%